Description of The Level of Knowledge of Adolescents Related to Reproductive Health in Prevention of Child Marriage to Reduce Stunting Rates in The Mandalika Special Economic Zone - Hardyningrat, Baiq Inna Dwi; Lina Nurbaiti; Fitriannisa Faradina Zubaidi (Jurnal Biologi Tropis, 2024)
Child marriage is the underlying cause of stunting, a condition in which children fail to grow to the expected adult height owing to persistent malnutrition. A couple or one of the participants in a child marriage must be under the age of 19. Knowledge related to reproductive health is everything that is known about health conditions in all matters relating to the reproductive system, its functions and processes. The study aims to determine the level of knowledge of 2nd grade high school students about reproductive health in preventing child marriage to reduce stunting rates in the Mandalika Special Economic Zone. This study is descriptive with a cross-sectional method. The respondents of this study were 112 2nd grade high school/vocational high school students in the Mandalika Special Economic Zone. The sample was taken using the simple random sampling method. Data analysis used univariate tests. The results showed that most respondents had a high level of knowledge about the reproductive system, sexual activity and sexually transmitted diseases, child marriage and its impacts, and stunting. The conclusion is that the level of adolescent knowledge about reproductive health in preventing child marriage to reduce stunting rates in the Mandalika Special Economic Zone is in the high category.